2017
DOI: 10.1016/j.jphs.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Arctiin protects against cardiac hypertrophy through inhibiting MAPKs and AKT signaling pathways

Abstract: In conclusion, arctiin can improve cardiac function and prevent the development of cardiac hypertrophy by blocking the MAPKs and AKT signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
0
26
1
Order By: Relevance
“…However, the effects of galangin on cardiac remodeling and the potential signaling mechanisms have not yet been elucidated. et al, 2006;J. Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of galangin on cardiac remodeling and the potential signaling mechanisms have not yet been elucidated. et al, 2006;J. Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…AKT mainly regulates cell survival and apoptosis. Recent studies have shown that PI3K-AKT signaling pathways play a considerable role in the process and pathogenesis of cardiac remodeling (J Li et al, 2017)…”
mentioning
confidence: 99%
“…Recent studies have emphasized the protective effect of arctiin in several disease models including has also been found to exert functions in protecting against endothelial cell damage, anti-Alzheimer' disease and antiaging, the antihair loss, and so on, and these bioactivities are closely related to the antioxidative stress effect of arctiin. Arctiin also protected against cardiac hypertrophy, and LPS induced acute lung injury via the inhibition of MAPKs/AKT and PI3K/AKT signaling pathways, respectively [ 39 , 40 ]. Although several researches have demonstrated that arctiin could play a vital role in strong response to oxidative stress, however, there are no reported studies on the protective effect of arctiin through the study in Nrf2 pathway, an important pathway of oxidative stress, have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal rat ventricular myocytes (NRVMs) were isolated from Sprague‐Dawley rats within 3 days of birth and cultured as previously described . Briefly, the hearts were quickly removed a; then, they were washed with phosphate‐buffered saline (PBS) three times, and incubated with 0.125% trypsin‐EDTA (Gibco, 2520‐072) for 15 minutes at 34°C for a total of five times.…”
Section: Methodsmentioning
confidence: 99%